An investigation of the educational needs of the American Indian of the southwest Oklahoma / - Nixon, William Ross (The University of Oklahoma., 1984)
This study established a description of the expressed needs of American Indian students as reported by school superintendents, parent advisory committee chairpersons, Indian students, and core teachers in public schools in Southwestern Oklahoma. The pertinent issues addressed in the study were (a) adequate and appropriate guidance and counseling of Indian students, (b) integration of the Indian heritage and culture into the existing curriculum, (c) appropriate examination of the financial management of federal monies as they apply to Indian education, and (d) the involvement of the Indian community in determining school policies and curriculum. The results of this study appear to indicate that Indian education is still suffering from certain practices and attitudes which have existed for hundreds of years. The data from this study indicate that administrators tend to occupy a positive position with regard to involvement with the Indian community on educational matters, that the parents recognize the need to become involved in the system to reach certain goals, and that the students seem to be attempting to bridge the gaps between two cultures. As for the teachers, they have become the force that perpetuates assimilation into the white society. It is their view that appears to not allow the Indian culture to be a part of the total educational scheme.
Keywords: Indians of North America Education.; Indians of North America Oklahoma.; Education, Administration.